2022
DOI: 10.3390/genes13112139
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the HD-Zip Gene Family and Dimerization Analysis of HB7 and HB12 in Brassica napus L.

Abstract: Homeodomain-leucine zipper (HD-Zip) genes encode plant-specific transcription factors, which play important roles in plant growth, development, and response to environmental stress. These genes have not been fully studied in allopolyploid Brassica napus, an important kind of oil crop. In this study, 165 HD-Zip genes were identified in B. napus and classified into four subfamilies. If proteins belong to the same subfamily, they exhibit similarities in gene structure, motifs, and domain distribution patterns. Bn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Many orthologs of ATHB genes from A. thaliana have been found in other plant species such as sunflower, tomato, cucumber, cotton, rice and Brassica (Lin et al 2008 ; Manavella et al 2008 ; Ariel et al 2010 ; Liu et al 2013 ; Zhang et al 2016 ; Yang et al 2020 ; Peng et al 2022 ). Despite their evolutionary relationship, they show only partial functional similarity at the transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many orthologs of ATHB genes from A. thaliana have been found in other plant species such as sunflower, tomato, cucumber, cotton, rice and Brassica (Lin et al 2008 ; Manavella et al 2008 ; Ariel et al 2010 ; Liu et al 2013 ; Zhang et al 2016 ; Yang et al 2020 ; Peng et al 2022 ). Despite their evolutionary relationship, they show only partial functional similarity at the transcriptional level.…”
Section: Introductionmentioning
confidence: 99%
“…Many genes in these plants are preferentially maintained in a duplicated state with very similar sequences, but they have gradually changed their functions by sub- or neofunctionalization (Chalhoub et al 2014 ; Babula-Skowrońska et al 2015 ; Jiang et al 2015 ). Recently, the expansion and expression patterns of HD-Zip genes in the Brassica species have been documented under different abiotic stress conditions (Jing et al 2017 ; Khan et al 2018 ; Peng et al 2022 ; Yin et al 2023 ). These studies showed dynamic changes in the expression patterns of homeobox genes in different tissues in relation to their response to abiotic stress and in the distribution of functional domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapeseed (Brassica napus L.) is one of the most important oilseed crops worldwide, with many agronomic advantages, such as rapid growth, high biomass productivity, and strong adaptability to diverse environmental conditions. Recent studies show that many protein families in rapeseed have potential functions to respond to salt and heavy-metal stresses, including cysteine-rich polycomb-like proteins (CPP) [30], homeodomain-leucine zipper proteins (HD-Zip) [31], heavy-metal ATPases (HMA) [32], and phosphorus transporters (PHT) [33]. B. napus is a moderately salt-tolerant species [34], and is a known heavymetal accumulator [35].…”
Section: Introductionmentioning
confidence: 99%